Cardiac magnetic resonance stress perfusion: A single-center study - Donato, P (2012)
INTRODUCTION AND OBJECTIVES: Myocardial ischemia can be assessed with cardiac magnetic resonance perfusion imaging (MRPI). This study aimed to analyze the clinical utility of MRPI in the diagnosis of significant coronary artery disease. METHODS: Fifty-five patients were examined with a 1.5 T MR scanner (Siemens Symphony), with a first pass of 0.10 mmol/kg gadolinium chelate, at rest and during adenosine vasodilatation (140μg/kg/min for 4min) using an inversion recovery steady-state free precession sequence. The results were compared with coronary angiography and with SPECT myocardial perfusion images. Agreement for qualitative diagnosis was measured by the kappa coefficient, taking statistical significance as 95%. Minimum clinical follow-up was 12 months. RESULTS: In 19 patients (34.5%) MRPI was negative for myocardial ischemia and necrosis, in 17 (30.9%) it was negative for ischemia but positive for necrosis, in 7 (12.7%) only ischemia was present and in 12 (21.8%) the ischemic area was larger than the necrotic area. The correlation between MRPI and coronary angiography for ischemia detection by coronary artery territory was very good: left anterior descending and right coronary - k=0.8571 (0.59-1), circumflex - k=0.8108 (0.59-1). By contrast, there was no correlation in terms of myocardial ischemia detection between MRPI and SPECT. CONCLUSIONS: MRPI is able to diagnose significant coronary disease in a high risk population, by detection of myocardial ischemia.